Understanding the genetic and physiological basis of drought resistance in Bambara groundnut (Vigna subterranea (L.) Verdc) - Salazar Licea, Luis Carlos (2022)
Bambara groundnut (Vigna subterranea (L) Verdc) is an underutilised African legume commonly known for its resistance to harsh environmental conditions such as drought, and equally known for its high protein content, and thus, having the potential to aid in the pursuit of food security as the climate is constantly changing. As an underutilised crop, Bambara groundnut has been relatively poorly researched in comparison to other more conventional crops such as maize, wheat, soybean, or rice.